QR Code Labeling Design for Fixed Asset Management in Accounting Information System PT. Cipta Jaya Perkasa - Marcelino S. Lawalata; Meilany Lengkey Kiet Tumiwa; Heidy Pesik; Edwin S. A. Lumunon (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
In an increasingly competitive world of work, the balance between work demands and employees' personal lives is an important issue that affects job satisfaction and productivity. The purpose of this research is to design a fixed asset accounting information system application using QR codes to facilitate inventory in bookkeeping. It can store more comprehensive data, on fixed asset data accurately in recording in each entity. The research method applied is the software development method using Prototyping, where the software creation process will be carried out module by module with testing, starting from tagging, and creating a unique QR code for each fixed asset in each existing entity. The result study results indicate that using technology can make it easier to record assets by simply scanning the QR Code label, which is attached to each asset. So that the process of recording or managing assets can run accurately and quickly. The output of the research is the creation of a web and mobile application to manage asset information systems by utilizing QR Code technology. The implication of this research is for companies to develop wellbeing programs that not only focus on stress reduction but also pay attention to the need for work-life balance. This research also contributes to the development of HR management theory in the context of employee welfare management in modern industries.